Marine propeller shaft loading analysis in moderate oblique-flow conditions. (15th October 2022) - Testa, C.; Greco, L.; Bosschers, J.
Abstract: Shaft loads of marine propellers in noncavitating oblique-flow conditions are herein investigated. The application of a Boundary Element Method (BEM) hydrodynamics is verified by the analysis of two propeller models, the highly-skewed DTMB 4679 and the unskewed INSEAN E779A, for which a comparison with experimental and numerical data is addressed. Whenever available, outcomes from PROCAL, a validated panel code solver developed by MARIN, and simulations from higher-fidelity CFD (Computational Fluid Dynamics) approaches, are used for comparison purposes. For moderate oblique-inflow angles, the comparison with experiments shows a good capability of the proposed BEM formulation in capturing unsteady blade pressures. In terms of shaft loads fluctuations, satisfactory results are carried out with respect to CFD outcomes. Moreover, it is found that averaged thrust and torque, as well as the lateral and vertical moments, are comparable with PROCAL predictions and in good agreement with CFD computations, whereas lateral forces suffer from the lack of a realistic estimation of viscous effects. Good estimates are also shown for the average location of thrust eccentricity, as long as the transverse loading on the hub is negligible. Highlights: Propeller shaft loads in oblique-flow conditions affect the bearings function of supporting engine rotor(s). Averaged shaft loads by BEM hydrodynamics are in good agreement with CFD results. Averaged lateral/vertical shaft forces suffer from the lack of a realistic viscous stress modelling. BEM hydrodynamics provides sectional pressure pulses in very good agreement with experiments and CFD. Shaft loads fluctuations by BEM and CFD are similar, albeit non-negligible differences may be present.